In the origin of language: From the need for food to the need for tolerance - Abdeddayem, SELLAMI; Alsaied, Mohamad Abdullah (Edelweiss Applied Science and Technology, 2024)
This research studies the relationship between humans and food and the development of language in a social context dating back to the beginnings of human history. The discovery of food represented the first moments that pushed humans to communicate with others, which in turn contributed to the emergence of language as a means of exchanging material and moral resources. Human language originated from the need to share food, accompanied by the development of communication from gestures to organized speech. Additionally, the research addresses the concept of generosity and solidarity in the context of food, noting that modern culture has affected these values. The research acknowledges that sharing food was a fundamental step towards building a human society based on cooperation and recognition of others' rights.